Off-design and annual performance analysis of supercritical carbon dioxide cycle with thermal storage for CSP application - Thanganadar, Dhinesh; Fornarelli, Francesco; Camporeale, Sergio; Asfand, Faisal; Patchigolla, Kumar (Elsevier, 2020)
Supercritical Carbon Dioxide (sCO2) cycles can achieve higher efficiency compared to steam-Rankine or Air-Brayton cycles, therefore they are promising for concentrated solar power applications. Although sCO2 cycles show higher design efficiency, the off-design efficiency is highly sensitive to the ambient conditions, impacting the power block net-power and heat input. In the present work a recompression sCO2 cycle is connected to a central-tower solar field with two-tank thermal storage delivering molten chloride salt at 670 °C. The temperature of the molten-salt exiting from the power block and returning to the cold storage tank increases by 46 °C with respect to the design value when the compressor inlet temperature is raised by 13 °C relative to the design condition of 42 °C, which implies that the capacity of the thermal storage reduces by 25%. The main focus of this work is to investigate the off-design performance of a sCO2 recompression cycle under variable ambient temperature, molten-salt inlet temperature and molten-salt flow rate. Multi-objective optimisation is carried-out in off-design conditions using an in-house code to explore the optimal operational strategies and the Pareto fronts were compared. Since the power cycle can either be operated in maximum power mode or maximum efficiency mode, this study compares these two operational strategies based on their annual performance. Results indicate that the capacity factor of the concentrated solar power can be increased by 10.8% when operating in maximum power mode whilst the number of start-ups is reduced by about 50% when operating in maximum efficiency mode.
Keywords: Supercritical CO2 cycle; CSP; Annual performance; Multi-objective optimisation; Thermal energy storage; Off-design